Evaluation of the Korean Weathex WxR-301D Radiosonde Against the Vaisala RS41: Temperature Consistency and Humidity Performance in Moist Environments - Byeongtaek Kim; Sungeun Hwang; Sora In; Youngtae Lee; Reno Choi; Jaewon Kim; Seonok Hong; Jaewon So; Kihoon Kim (Asia-Pacific Journal of Atmospheric Sciences, 2026)
Radiosondes are essential for atmospheric profiling, offering high-resolution observations of thermodynamic and kinematic parameters. This presents a comparative assessment of the Vaisala RS41 and the Weathex (Korean company) WxR-301D radiosondes based on 46 dual soundings conducted during a summer field campaign over Jeju Island, South Korea. Simultaneous temperature and relative humidity measurements were analyzed under diverse synoptic conditions, including clear, cloudy, foggy, and rainy cases. The RS41 and WxR-301D exhibited strong agreement in temperature measurements, with a mean absolute error of 1.19 °C across altitude and diurnal cycles. However, humidity observations revealed systematic differences: the WxR-301D exhibited increased variability and a tendency to overestimate humidity under rainy conditions, particularly in the upper troposphere and lower stratosphere. An ISSR-based case analysis further revealed pronounced discrepancies in humidity profiles between the two radiosondes. While the RS41 indicated a realistic drying trend within and above the ISSR, the WxR-301D maintained elevated humidity values exceeding 60% in the stratosphere, suggesting possible sensor wetting or icing effects, or measurement lag. These results highlight the importance of evaluating the performance of unheated humidity sensors under cold and moist atmospheric conditions. The results provide a basis for refining operational radiosonde quality control and sensor calibration protocols.

Evolution-aided improvement of the acid tolerance of Levilactobacillus brevis and its application in sourdough fermentation - Na Ree Han; Sora Yu; Jung A Byun; Eun Ju Yun; Seongwon Cheon; Seongbong Song; Sangmin Shim; In-Geol Choi; Sung-Ho Lee; Kyoung Heon Kim (Food Research International, 2024)